Biophysical Profiling of Tumor Cell Lines - Frederick Coffman; Rachid Hamid; Marion C. Cohen; Ralph Garippa; Stanley Cohen (Analytical Cellular Pathology)
Despite significant differences in genetic profiles, cancer cells share common phenotypic properties, including membrane-associated changes that facilitate invasion and metastasis. The Corning Epic® optical biosensor was used to monitor dynamic mass rearrangements within and proximal to the cell membrane in tumor cell lines derived from cancers of the colon, bone, cervix, lung and breast. Data was collected in real time and required no exogenously added signaling moiety (signal-free technology). Cell lines displayed unique profiles over the time-courses: the time-courses all displayed initial signal increases to maximal values, but the rate of increase to those maxima and the value of those maxima were distinct for each cell line. The rate of decline following the maxima also differed among cell lines. There were correlations between the signal maxima and the observed metastatic behavior of the cells in xenograft experiments; for most cell types the cells that were more highly metastatic in mice had lower time-course maxima values, however the reverse was seen in breast cancer cells. The unique profiles of these cell lines and the correlation of at least one profile characteristic with metastatic behavior demonstrate the potential utility of biophysical tumor cell profiling in the study of cancer biology.